2022
DOI: 10.5194/gmd-15-6399-2022
|View full text |Cite
|
Sign up to set email alerts
|

AWI-CM3 coupled climate model: description and evaluation experiments for a prototype post-CMIP6 model

Abstract: Abstract. We developed a new version of the Alfred Wegener Institute Climate Model (AWI-CM3), which has higher skills in representing the observed climatology and better computational efficiency than its predecessors. Its ocean component FESOM2 (Finite-volumE Sea ice–Ocean Model) has the multi-resolution functionality typical of unstructured-mesh models while still featuring a scalability and efficiency similar to regular-grid models. The atmospheric component OpenIFS (CY43R3) enables the use of the latest dev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 104 publications
1
15
0
Order By: Relevance
“…After the initialization, the pan-hemispheric sea ice model performance is similar for the three configurations, and attributing the error differences to the use of different model resolution or complexity is not obvious, confirming previous findings (e.g., Streffing et al 2022;Selivanova et al, 2023). Overall, the model errors for the first year of simulations are in line with state-of-the-art seasonal prediction systems (Johnson et al 2019;Mu et al 2020;Mu et al 2022),…”
Section: Integrated Sea Ice Performance Metricssupporting
confidence: 84%
“…After the initialization, the pan-hemispheric sea ice model performance is similar for the three configurations, and attributing the error differences to the use of different model resolution or complexity is not obvious, confirming previous findings (e.g., Streffing et al 2022;Selivanova et al, 2023). Overall, the model errors for the first year of simulations are in line with state-of-the-art seasonal prediction systems (Johnson et al 2019;Mu et al 2020;Mu et al 2022),…”
Section: Integrated Sea Ice Performance Metricssupporting
confidence: 84%
“…Besides the uncertainty from the comparison between the equilibrium simulation and the transient observation and CMIP6 results, we could not run the high‐resolution AWI‐CM3 simulations for enough model years as the typical CMIP6 simulations to fully reach equilibrium states, which also induces uncertainties to this study. Despite those, Streffing et al (2022) showed that the AWI‐CM3 transient simulation with TCo159 already outperforms CMIP6 in many large‐scale climatologies, and features above CMIP6‐average skills. We here confirm this conclusion for specific aspects of more regional climate (i.e., the East Asian precipitation), although model setups different from those employed by Streffing et al (2022) are applied.…”
Section: Discussionmentioning
confidence: 97%
“…Despite those, Streffing et al (2022) showed that the AWI‐CM3 transient simulation with TCo159 already outperforms CMIP6 in many large‐scale climatologies, and features above CMIP6‐average skills. We here confirm this conclusion for specific aspects of more regional climate (i.e., the East Asian precipitation), although model setups different from those employed by Streffing et al (2022) are applied. Furthermore, we conclude that employing AWI‐CM3 at a higher spatial resolution of the atmosphere model indeed improves the simulation of the EAP.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations